2020
DOI: 10.1186/s13195-020-00614-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and tolerability of atabecestat (JNJ-54861911), an oral BACE1 inhibitor, in early Alzheimer’s disease spectrum patients: a randomized, double-blind, placebo-controlled study and a two-period extension study

Abstract: Background: Atabecestat, a potent brain-penetrable inhibitor of BACE1 activity that reduces CSF amyloid beta (Aβ), was developed for oral treatment for Alzheimer's disease (AD). The long-term safety and effect of atabecestat on cognitive performance in participants with predementia AD in two phase 2 studies were assessed. Methods: In the placebo-controlled double-blind parent ALZ2002 study, participants aged 50 to 85 years were randomized (1:1:1) to placebo or atabecestat 10 or 50 mg once daily (later reduced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 22 publications
0
46
0
1
Order By: Relevance
“…21 MRI analyses of brain volumes after atabecestat exposure in people with preclinical AD and MCI due to AD did not show a clear treatment-related difference. 22 Significantly greater decrease in whole brain volume was observed for lanabecestat 20 mg and 50 mg groups in (A) AMARANTH and for lanabecestat 50 mg group in (B) DAYBREAK-ALZ compared to placebo. Significantly greater decrease in hippocampal volume was observed for lanabecestat 20 mg and 50 mg groups compared to placebo in (C) AMARANTH, but not in (D) DAYBREAK-ALZ.…”
Section: Effects Of Lanabecestat Treatment On Neuroimaging Assessmentsmentioning
confidence: 98%
“…21 MRI analyses of brain volumes after atabecestat exposure in people with preclinical AD and MCI due to AD did not show a clear treatment-related difference. 22 Significantly greater decrease in whole brain volume was observed for lanabecestat 20 mg and 50 mg groups in (A) AMARANTH and for lanabecestat 50 mg group in (B) DAYBREAK-ALZ compared to placebo. Significantly greater decrease in hippocampal volume was observed for lanabecestat 20 mg and 50 mg groups compared to placebo in (C) AMARANTH, but not in (D) DAYBREAK-ALZ.…”
Section: Effects Of Lanabecestat Treatment On Neuroimaging Assessmentsmentioning
confidence: 98%
“…Given the potential clinical significance and market effects of AD therapeutics, there have been many attempts to target Aβ using various approaches focusing on different stages of the amyloid cascade ( Table 1 ) [ 185 - 228 ]. For example, inhibitors of Aβ-related secretases aim to decrease the production of Aβ itself as a preventative measure, while anti-Aβ immunotherapies induce partial or complete clearance of Aβ at the end of the amyloid cascade.…”
Section: Aβ-directed Therapeutics In Clinical Trials and Implicationsmentioning
confidence: 99%
“…It inhibits APP cleavage by the enzyme BACE and thus reduces Aβ level in cerebrospinal fluid (CSF). Results of long-term safety and tolerability of atabecestat in the early AD patients evaluated through a randomized, double-blind, placebo-controlled study and a two-period extension study showed it to be associated with a trend toward declines in cognition, and elevation of liver enzymes [ 54 ].…”
Section: Therapeutic Strategies For the Development Of Anti-ad Drugsmentioning
confidence: 99%